2022
DOI: 10.1364/ol.450696
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-optic joint time and frequency transmission with enhanced time precision

Abstract: We propose a high-precision joint time and frequency transmission scheme based on bidirectional wavelength division multiplexing transmission over an optical fiber link. The time signal is generated based on the phase-stable frequency signal with employment of a dedicated designed low-jitter event generator. Time synchronization is realized by eliminating the time difference between the time signals of the master and slave stations, which is determined by accurate two-way time comparison. In this way, thanks t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…With active compensation based on an optical delay line, the frequency instability 5:9 × 10 −17 at 10,000 s over a 106-km urban fiber link is obtained. Much excellent research has been done on long distance optical frequency [22] , radio frequency [23,24] , time [25,26] , and simultaneous transmission [27][28][29][30][31] . All of the present research is focused on the joint transmission of metrological signals over longer or more complex optical fiber links.…”
Section: Introductionmentioning
confidence: 99%
“…With active compensation based on an optical delay line, the frequency instability 5:9 × 10 −17 at 10,000 s over a 106-km urban fiber link is obtained. Much excellent research has been done on long distance optical frequency [22] , radio frequency [23,24] , time [25,26] , and simultaneous transmission [27][28][29][30][31] . All of the present research is focused on the joint transmission of metrological signals over longer or more complex optical fiber links.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers studying high-precision fiber-optic timefrequency transmission [9][10][11][12], the time-frequency transmission method with the highest transmission accuracy attainable currently, have made significant progress in applications independent of Ethernet. Beloy et al [13] reported a network comparison of three optical clocks, with fractional ratio uncertainties between 6 × 10 −18 and 8 × 10 −18 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, signal transfer over optical fiber has been established as a solution to surpass the stability and accuracy of GNSS links [5]. Recent work has demonstrated timing signal transfer with compensation of fiber-length variation over dark channels of commercial communications fiber [6], [7], [8] and packet-based methods such as ''White Rabbit'' [9].…”
Section: Introductionmentioning
confidence: 99%